Pengaruh Belanja Daerah Terhadap Pembangunan Manusia di Pulau Sumatera Tahun 2019-2023 - Dwi Nofitri, Fany; Elvira, Rini (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2024)
This study aims to test and see whether regional spending with capital expenditure indicators has an influence on human development with the Human Development Index (HDI) indicator on the island of Sumatra in 2019-2023. Secondary data is used with data collection techniques, namely through documentation of publication data sourced from several official websites of government agencies such as the Central Statistics Agency (BPS) for Human Development Index (HDI) data and the Directorate General of Fiscal Balance (DJPK) for capital expenditure data in all provinces on the island of Sumatra from 2019-2023. The data analysis technique used is simple linear regression. The results obtained show that capital expenditure has a significant negative effect on the Human Development Index (HDI) on the island of Sumatra. Also, the results of the coefficient of determination of capital expenditure have an effect of 0.080 equal to 8 percent on the Human Development Index (HDI). This means that 8 percent of human development (HDI) is influenced by regional expenditure (capital expenditure). While the remaining 92 percent is influenced by other factors not examined. Keywords: regional expenditure, capital expenditure, human development, HDI